2013
DOI: 10.1371/journal.pone.0073398
|View full text |Cite
|
Sign up to set email alerts
|

Representation of Women and Pregnant Women in HIV Research: A Limited Systematic Review

Abstract: BackgroundHIV-related outcomes may be affected by biological sex and by pregnancy. Including women in general and pregnant women in particular in HIV-related research is important for generalizability of findings.ObjectiveTo characterize representation of pregnant and non-pregnant women in HIV-related research conducted in general populations.Data SourcesAll HIV-related articles published in fifteen journals from January to March of 2011. We selected the top five journals by 2010 impact factor, in internal med… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 47 publications
2
7
0
Order By: Relevance
“…This is a concerning gap considering that both sex- and drug-related HIV risk behaviors are common among pregnant women who abuse substances (Baker et al, 2001; Ramsey, Bell, & Engler-Field, 2010), and if infected with HIV, pregnant women can infect their child via vertical transmission. This finding is in accordance with another systematic review that revealed that pregnant women tend to be underrepresented in HIV/AIDS research (Westreich et al, 2013). Second, results from our study suggest that no studies during the last 10 years have been conducted with women 15 to 17 years old who abuse substances, which is concerning since HIV is one of the leading causes of death among women as young as 15 through age 49 throughout the world (World Health Organization, 2013).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is a concerning gap considering that both sex- and drug-related HIV risk behaviors are common among pregnant women who abuse substances (Baker et al, 2001; Ramsey, Bell, & Engler-Field, 2010), and if infected with HIV, pregnant women can infect their child via vertical transmission. This finding is in accordance with another systematic review that revealed that pregnant women tend to be underrepresented in HIV/AIDS research (Westreich et al, 2013). Second, results from our study suggest that no studies during the last 10 years have been conducted with women 15 to 17 years old who abuse substances, which is concerning since HIV is one of the leading causes of death among women as young as 15 through age 49 throughout the world (World Health Organization, 2013).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, consuming alcohol and smoking, ingesting, or inhaling drugs such as alcohol, crack cocaine, methamphetamine, and amyl nitrite (poppers) are also associated with increased risk for HIV infection by reducing users’ inhibitions to engage in risky sexual behavior, impairing judgment, and enhancing libido (Colfax & Shoptaw, 2005; Des Jarlais et al, 2007; Walley, Krupitsky, & Cheng, 2008). Exchange of sex for drugs or money, another risk factor for HIV infection, is common among those who abuse injection and non-injection drugs (Baker, Heather, Wodak, & Lewin, 2001; Draus & Carlson, 2009; El-Bassel et al, 1997; Inciardi, 1995; Meader et al, 2013; Westreich, Rosenberg, Schwartz, & Swamy, 2013). Of note, the risk of becoming infected with HIV via needle sharing varies in different parts of the world.…”
mentioning
confidence: 99%
“…Nevertheless, pregnant women remain under-represented within general HIV prevention, treatment, and care studies. 54 Furthermore, as efforts to eliminate vertical HIV transmission expand, including growing access to lifelong antiretroviral therapy for pregnant women independent of CD4 staging to optimize their own health outcomes as well as the child's, building the evidence base of effective interventions to reduce loss to follow-up among post-partum women and infants is needed. 55 Infant and child survival depend on the long-term health outcomes of mothers, and human rights-affirming approaches to support the health of mothers living with HIV will also optimize family health outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…Mirroring gaps discussed in the literature [19, 20, 21], they identified areas of need including pregnancy safety and dosing information for newer ARVs; optimal treatment following PMTCT; safety and efficacy of emerging preventive strategies, such as microbicides, vaginal rings, oral pre-exposure prophylaxis (PrEP), and vaccines; treatment for HIV co-infections, including tuberculosis and malaria; as well as guidance for diagnostics. One commonly cited example was efavirenz, for which a lack of safety data in pregnancy resulted in reticence to use the drug, leading not only to limited treatment options for pregnant women, but also potentially poorer health outcomes given regimen changes and adverse effects associated with alternative ARVs.…”
Section: Roadblocks To Researchmentioning
confidence: 99%